Aju tiheliiduste valkude ekspressioon sepsise korral lahangumaterjalis - Erikson, Kristo; Tuominen, Hannu; Vakkala, Merja; Liisanantti, Janne Henrik; Karttunen, Tuomo; Syrjälä, Hannu; Ala-Kokko, Tero Ilmari (Eesti Arst, 2021)
Eesti Arst 2021; 100(8):453